Novel control system applied in the modernization of public lighting systems in heritage cities: Case study of the City of Cuenca. (November 2022) - Galindo, Santiago Pulla; Borge-Diez, David; Icaza, Daniel
Abstract: Several heritage cities face the need to modernize public lighting systems that are installed on the facades of buildings. The legal obstacles to intervene in heritage infrastructures create a different scenario than other cities. This circumstance raises the question if it is possible to install a modern, innovative lighting system, isolated from the electrical distribution system. This research analyzes the feasibility of modernizing the system using 304 mini photovoltaic generation plants, implementing a novel lighting system control process that indirectly uses sky brightness measurements based on current research at the Catholic University of Cuenca. As a case study, the Historic Center of the City of Cuenca-Ecuador, a World Heritage Site, whose system is made up of 1, 252 luminaires, is analyzed. The results conclude that it is feasible to modernize the lighting service with the adoption of the proposed technologies and for control, a novel system based on indirect measurement of sky clarity has been developed. Finally, the political implications are analyzed in the framework of energy efficiency and modernization of the systems, as well as the recommendation to the political decision-makers. The study can be replicated in other cities of the world with similar characteristics. Graphical abstract: Highlights: Several heritage cities need to replace public lighting systems: specific solutions are required. These cities have HPS lighting systems that must be replaced by LED systems. Government regulations restrict greater interventions in heritage infrastructure. Case study for Cuenca (Ecuador): 425 mini isolated systems with LED and a PV source. The systems will be integrated with smart lighting, smart city and IoT systems.